2017
DOI: 10.3347/kjp.2017.55.1.9
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of Toxoplasmosis Detected by RDT among the Residents of Seokmo-do (Island) in Ganghwa-Gun, Incheon City, Korea

Abstract: Seroprevalence of Toxoplasma gondii infection among the residents of Seokmo-do (Island) in Ganghwa-gun, Incheon, Korea was surveyed for 4 years by a rapid diagnostic test (RDT) using recombinant fragment of major surface antigen (SAG1), GST-linker-SAG1A. Sera from 312, 343, 390, and 362 adult residents were collected on a yearly basis from 2010 to 2013, respectively. Total positive seroprevalence regardless of gender was 29.2, 35.3, 38.7, and 45.3% from 2010 to 2013, respectively. Positive seroprevalence in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Four-year follow-up study in Ganghwa and Cheorwon reported seroprevalence escalated during the study period, and the infection rate was higher in men than women [ 17 ]. Sukmo Island study also reported similar results that it observed rise in seroprevalence and higher prevalence in men than women [ 18 ]. Previous studies had shown that the seroprevalence is increasing, but there has been no study explored regional difference in seroprevalence.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Four-year follow-up study in Ganghwa and Cheorwon reported seroprevalence escalated during the study period, and the infection rate was higher in men than women [ 17 ]. Sukmo Island study also reported similar results that it observed rise in seroprevalence and higher prevalence in men than women [ 18 ]. Previous studies had shown that the seroprevalence is increasing, but there has been no study explored regional difference in seroprevalence.…”
Section: Introductionsupporting
confidence: 56%
“…According to studies conducted in Ganghwa and Cheorwon from 2010 to 2013, men’s prevalence in both regions was 1.5 times higher than that of women [ 17 , 18 ]. Previous studies have speculated that this phenomenon is due to the fact that men are more active in socioeconomic activities than women in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The structurally modified rSAG1A-GRA2-based RDT showed 100% specificity and 97.1% sensitivity for detection of human Toxoplasma infection as compared to a laboratory ELISA that used T. gondii whole cell lysate antigen [36]. An RDT kit comprising GST-linked SAG1A has been used to detect Toxoplasma infection in Seokmo-do (Island) in Ganghwa-gun, Incheon City, South Korea [51].…”
Section: Lateral Flow Assaymentioning
confidence: 99%
“…RDT data with address of subjects from Gyodong-myeon and Samsan-myeon was obtained from preceding studies, and the number of patients in each region is summarized in the Table 1 [ 11 , 12 ]. IgG/IgM RDT mounted with recombinant fragment of major surface antigen (SAG1A), GST-linker-SAG1A, were applied to the sera mentioned above [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seroprevalence of toxoplasmosis in certain areas is surging recently [ 10 13 ]. Previous studies have shown that the overall proportion, gender and age distribution of Gyodong-myeon and Samsan-myeon [ 11 , 12 ]. In addition to this, if clusters with high risk are specified by comparing them to each region, efficient monitoring and health policies can be established accordingly.…”
Section: Introductionmentioning
confidence: 99%